Cutaneous Leishmaniasis Hampers COVID-19: A Controlled Cross-Sectional Study in High-Burden Endemic Areas of Iran - Mehdi Bamorovat; Iraj Sharifi; Mehdi Shafiei Bafti; Setareh Agha Kuchak Afshari; Mohammad Reza Aflatoonian; Ali Karamoozian; Abdollah Jafarzadeh; Raheleh Amirzadeh; Ahmad Khosravi; Zahra Babaei; Farzane Safa; Fatemeh Sharifi; et al. (Springer, 2024)
Abstract Introduction Emerging infectious diseases such as SARS-CoV-2 can cause pandemics and create a critical risk for humans. In a previous pilot study, we reported that the immunological responses induced by cutaneous leishmaniasis (CL) could decrease the incidence and severity of COVID-19. In this large-scale case-control study, we assessed the possible relationship between mortality and morbidity of COVID-19 in healed CL persons suffering scars compared to cases without CL history. Methods This controlled cross-sectional study was conducted between July 2020 and December 2022 in the endemic and high-burden areas of CL in southeastern Iran. In the study, 1400 previous CL cases with scars and 1,521,329 subjects who had no previous CL were analyzed. We used R 4.0.2 to analyze the data. Firth's bias reduction approach corresponding to the penalization of likelihood logistic regression by Jeffreys was also employed to influence the variables in the dataset. Also, a Bayesian ordinal logistic regression model was performed to explore the COVID-19 severity in both case and referent groups. Results The occurrence and severity rate of COVID-19 in CL scar cases are significantly less than in the non-CL control group, while in the CL scar subjects, patients with critical conditions and mortality were not observed. The morbidity (OR = 0.11, CI 0.06-0.20 and P < 0.001) and severity of COVID-19 in previous cases with CL scars were significantly diminished than that in the control group (credible interval − 2.57, − 1.62). Conclusions The results represented a durable negative relationship between cured CL and COVID-19 incidence and severity. Additional studies seem necessary and should be designed to further validate the true impact and underlying mechanistic action of CL on COVID-19. Graphical abstract